Associations of cardiovascular fat radiodensity and vascular calcification in midlife women: The SWAN cardiovascular fat ancillary study. (December 2018) - Hanley, Carrie; Shields, Kelly J.; Matthews, Karen A.; Brooks, Maria M.; Janssen, Imke; Budoff, Matthew J.; Sekikawa, Akira; Mulukutla, Suresh; El Khoudary, Samar R.
Abstract: Background and aims: Fat radiodensity, measured via CT Hounsfield units (HU), is a potential marker of fat quality. We sought to determine the cross-sectional associations of total heart fat (TAT) and aortic perivascular fat (PVAT) radiodensity with cardiovascular risk factors, coronary artery calcification (CAC), and aortic calcification (AC) in midlife women. Methods: Fat radiodensity, CAC, and AC were quantified using CT scans. A total of 528 women (mean age: 50.9 ± 2.9 years; 37% Black) were included in analyses. Results: Women in the lowest TAT radiodensity tertile were more likely to have adverse cardiovascular risk factors. Independent of cardiovascular risk factors, women in the middle and high TAT radiodensity tertiles were less likely to have CAC (OR (95% CI): 0.32 (0.18, 0.59); 0.43 (0.24, 0.78), respectively) compared with women in the lowest TAT radiodensity tertile. Although adjusting for BMI attenuated the overall association, women in the middle TAT radiodensity tertile remained at significantly lower odds of CAC when compared to the low radiodensity tertile, 0.47 (0.24, 0.93), p =0.03. No significant associations were found for PVAT radiodensity and calcification measures in multivariable analysis. Conclusions: Lower TAT radiodensity was associated with a less favorable cardiometabolic profile. Women with mid-range TAT radiodensity values had a lower odds of CAC presence, independent of CVD risk factors and BMI. More research is necessary to understand radiodensity as a surrogate marker of fat quality in midlife women. Highlights: Lower TAT and PVAT radiodensities are associated with a less favorable CVD risk profile in midlife women. Women with mid-range TAT radiodensity have lower odds of CAC presence independent of risk factors and BMI. Our study showed PVAT radiodensity is not related to CAC or AC in women at midlife.